Steady state non-Newtonian flow with strain rate dependent viscosity in domains with cylindrical outlets to infinity - Panasenko, Grigory; Pileckas, Konstantin; Vernescu, Bogdan (Nonlinear Analysis: Modelling and Control, 2021)
The paper deals with a stationary non-Newtonian flow of a viscous fluid in unbounded domains with cylindrical outlets to infinity. The viscosity is assumed to be smoothly dependent on the gradient of the velocity. Applying the generalized Banach fixed point theorem, we prove the existence, uniqueness and high order regularity of solutions stabilizing in the outlets to the prescribed quasi-Poiseuille flows. Varying the limit quasi-Poiseuille flows, we prove the stability of the solution.